Penerapan Program Usaha Kesehatan Sekolah (UKS) Di Madrasah Aliyah Kiay Modjo Ikhwan - Julia Djamal; Cindy Mayulu; Moh Djenaan; Ripana Lakoro; Liliana Buntuan; Celine Kiantjili (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Implementation of the School Health Business Program (UKS), namely school-based health services which include preventiveefforts, early detection, and interventions forchildren’s physical social and mental health. The purpose implementing the school health business program is to improve the health of the school environment, improve a culture of healthy living behavior that contributes to the physical and psychological health status of students and teachers at Madrasah Aliyah KiayModjo Ikhwan. This activity targets 30 students and teachers in schools. Madrasah Aliyah Kiay  Modjo Ikhwan students were the targets of this activity. Activities carried out in the form of conselling, room arrangement, as well as health.